2018
DOI: 10.3390/app8122409
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Propagation Characteristics of Hazardous Noxious Substances Spilled from Transport Ships

Abstract: This study numerically investigates the propagation characteristics of hazardous noxious substances (HNSs) spilled from transport ships and suggests the metal model for predicting the HNS propagation velocity varied with the current velocity and HNS density. The commercial computational fluid dynamics (CFD) code ANSYS FLUENT (V. 17.2) was used for two-dimensional simulation based on the Reynolds-averaged Navier–Stokes (RANS) equation together with the standard k–ε model. The scalar transport equation was also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…• Crude oils • Refined oil products (e.g., gasoline, diesel fuel, aviation fuel) • Vegetable oils • Other types of oil (marine gas oil, marine diesel oil, heavy fuels oil) The exact negative effects of a potential spill of these substances depend on environmental factors, including weather conditions, the spill location, the properties of the hazardous substance itself, and the way these are packaged and stowed [50]. The behavior of HNSs and oil spills is also different [48,53]. For example, when oil is spilled in water, it tends to spread out, moving on the water's surface because of the effect of wind and currents, presenting changes in its physical and chemical properties, such as specific gravity, viscosity, distillation, and pour point.…”
Section: Examples Of Oil Shipmentsmentioning
confidence: 99%
“…• Crude oils • Refined oil products (e.g., gasoline, diesel fuel, aviation fuel) • Vegetable oils • Other types of oil (marine gas oil, marine diesel oil, heavy fuels oil) The exact negative effects of a potential spill of these substances depend on environmental factors, including weather conditions, the spill location, the properties of the hazardous substance itself, and the way these are packaged and stowed [50]. The behavior of HNSs and oil spills is also different [48,53]. For example, when oil is spilled in water, it tends to spread out, moving on the water's surface because of the effect of wind and currents, presenting changes in its physical and chemical properties, such as specific gravity, viscosity, distillation, and pour point.…”
Section: Examples Of Oil Shipmentsmentioning
confidence: 99%
“…In addition, we used the well-known standard k-ε model. In our previous study, we conducted simulation to evaluate the CFD methods and compared the predictions with measured data obtained in with the lab-scale oil spill experiment [12,13]. This experiment was conducted by Tavakoli et al [13] who provided the 3 of 14 measured data for oil propagation in the oil tank under different scenarios.…”
Section: Cfd Simulationmentioning
confidence: 99%
“…Hence, information within 1 km of the ship cannot be yielded, and, accordingly, cannot contribute to the early response stage of the HNS spill in detail. Previously, our group conducted a two-dimensional CFD simulation for predicting the near-field propagation behavior in the vicinity of the ship, within a few hundred meters [12], and presented the spatial HNS distribution over time.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the present study extensively conducted CFD simulations for different cases and it suggested important parameters that can be used to mathematically connect inputs and outputs. Previously, a regression model was reported and tested with the CFD simulation results [12,13]. The current study aimed to construct the metamodel with the simulation results for 80 scenarios.…”
Section: Introductionmentioning
confidence: 99%